2022
DOI: 10.1038/s41594-021-00718-y
|View full text |Cite
|
Sign up to set email alerts
|

Seipin forms a flexible cage at lipid droplet formation sites

Abstract: Lipid droplets (LDs) form in the endoplasmic reticulum by phase separation of neutral lipids. This process is facilitated by the seipin protein complex, which consists of a ring of seipin monomers, with a yet unclear function. Here, we report a structure of S. cerevisiae seipin based on cryogenic-electron microscopy and structural modeling data. Seipin forms a decameric, cage-like structure with the lumenal domains forming a stable ring at the cage floor and transmembrane segments forming the cage sides and to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…How these ER proteins, but not others, access forming LDs is unclear. Current data suggest that the oligomeric seipin ring at LDACs restricts some proteins from accessing nascent LDs 55 57 while permitting others (Fig. 7d ).…”
Section: Discussionmentioning
confidence: 92%
“…How these ER proteins, but not others, access forming LDs is unclear. Current data suggest that the oligomeric seipin ring at LDACs restricts some proteins from accessing nascent LDs 55 57 while permitting others (Fig. 7d ).…”
Section: Discussionmentioning
confidence: 92%
“…It is difficult to overstate the contribution of yeast systematic genetics approaches to our current understanding of eukaryotic lipid metabolism and LD biology ( Radulovic et al, 2013 ). A few recent examples include: insights onto the regulated dynamics and spatial positioning of LDs during nutrient stress conditions to supply free fatty acids ( Henne et al, 2018 ; Hariri et al, 2019 ); the first mechanistic and structural descriptions of the seipin complex driving LD budding from the ER ( Klug et al, 2021 ; Arlt et al, 2022 ), and systematic screens for its regulatory partners ( Eisenberg-Bord et al, 2018 ); the description of specific mechanisms by which LDs contribute to manage protein aggregates ( see also below ) ( Moldavski et al, 2015 ); or the discovery of a new class of LDs stemming from nuclear membranes ( Romanauska and Köhler, 2018 ). Innovative applications of imaging technologies for automated screening, such as 3D imaging ( Lv et al, 2019 ), have also been reported in this system.…”
Section: Ld Functional Genomics: Screening For Ld Biogenesis Function...mentioning
confidence: 99%
“…On the ER, the accumulation of PA increases surface tension and decreases line tension of local ER, impeding unidirectional LD budding and normal ER-LD contact [ 32 ]. (2) The structural role of seipin in TAG and diacylglycerol (DAG) facilitates TAG phase separation, LD budding, and growth [ 33 , 34 , 35 ]. Seipin protein complex not only captures TAG and DAG inside its ring, but also provides TAG clusters for multiple nucleation sites [ 33 , 34 ].…”
Section: Structure and Physiological Function Of Seipinmentioning
confidence: 99%
“…Seipin protein complex not only captures TAG and DAG inside its ring, but also provides TAG clusters for multiple nucleation sites [ 33 , 34 ]. Recently, the seipin protein complex has also been found to form a flexible cage-like structure, and the dynamic conformation changes in this structure contribute to the TAG phase separation, as well as LD growth and budding [ 35 ]. (3) Compelling evidence indicates that seipin plays a key role in the structure of ER-LD contact to promote the biogenesis or maintenance of LDs [ 4 , 36 , 37 , 38 , 39 ].…”
Section: Structure and Physiological Function Of Seipinmentioning
confidence: 99%
See 1 more Smart Citation